2009
DOI: 10.1097/pas.0b013e3181b8cf03
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Histologic Assessment Helps to Differentiate Multiple Lung Primary Nonsmall Cell Carcinomas From Metastases

Abstract: The pathological classification of non-small cell lung cancer (NSCLC) is evolving. Lung adenocarcinoma is morphologically heterogeneous, with mixtures of acinar, papillary, bronchioloalveolar and solid patterns in more than 80% of cases. In case of synchronous or metachronous multiple NSCLC, the distinction of intrapulmonary metastases from independent primary tumors is of great clinical importance since it influences staging and potentially the therapeutic strategy. Here we took advantage of a cohort of 20 pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
219
1
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 231 publications
(240 citation statements)
references
References 19 publications
(27 reference statements)
9
219
1
2
Order By: Relevance
“…Similar to previously published studies, in our study histo-molecular characterization correlated with Martini-Melamed criteria in about 50% of the cases, including both adenocarcinoma and squamous cell carcinoma. 4,5,9,16,17 This is not surprising as morphological subtying of lung adenocarcinoma has changed in the past decade, and the proposed detailed approach has been implemented in the 2015 World Health Organization classification of lung tumors. 18 Adenocarcinoma of the lung is morphologically heterogenous and careful comparison of morphological subtypes between two tumors is potentially useful in staging of synchronous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…Similar to previously published studies, in our study histo-molecular characterization correlated with Martini-Melamed criteria in about 50% of the cases, including both adenocarcinoma and squamous cell carcinoma. 4,5,9,16,17 This is not surprising as morphological subtying of lung adenocarcinoma has changed in the past decade, and the proposed detailed approach has been implemented in the 2015 World Health Organization classification of lung tumors. 18 Adenocarcinoma of the lung is morphologically heterogenous and careful comparison of morphological subtypes between two tumors is potentially useful in staging of synchronous tumors.…”
Section: Discussionmentioning
confidence: 99%
“…It may also be helpful in staging evaluation of multiple nodules to compare histological patterns of adenocarcinoma within different tumor nodules. 33 In addition, the future holds expansion of insights into molecular pathogenesis that may have morphological associations.…”
Section: Invasive Adenocarcinoma Patternsmentioning
confidence: 99%
“…4) Girard et al concluded comprehensive histologic assessment methodology is a powerful tool in determining whether multiple adenocarcinomas or squamous cell carcinomas are metastatic or multiple primaries. 5) In their series, however, the diagnoses based on the methodology were inconsistent with molecular characterization results in 2 (9%) of the 22 comparison pairs. Based on their methodology, our case is diagnosed as double primaries, but both tumors had the same EGFR mutation.…”
Section: Discussionmentioning
confidence: 99%